2016
DOI: 10.3389/fncel.2016.00246
|View full text |Cite
|
Sign up to set email alerts
|

GluN2A Subunit-Containing NMDA Receptors Are the Preferential Neuronal Targets of Homocysteine

Abstract: Homocysteine (HCY) is an endogenous redox active amino acid, best known as contributor to various neurodegenerative disorders. Although it is known that HCY can activate NMDA receptors (NMDARs), the mechanisms of its action on receptors composed of different NMDA receptor subunits remains almost unknown. In this study, using imaging and patch clamp technique in cultured cortical neurons and heterologous expression in HEK293T cells we tested the agonist activity of HCY on NMDARs composed of GluN1 and GluN2A sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 43 publications
4
41
0
1
Order By: Relevance
“…Previously, Lecleric et al evidenced the occurrence of NMDA receptor in PC12 cells and concluded that PC12 cells express predominantly the splice variant NMDAR1-4a and smaller amounts of NMDAR1-1a, NMDAR1-2a, and NMDAR1-3a [35]. More recently, Sibarov et al implicated that GluN2A subunit-containing NMDA receptors as the preferential neural targets of Hcy [36]. Moreover, Hcy has been confirmed not only to be Ca 2+ -and NMDA receptor-dependent, but also Ca 2+ -independent, mainly mediated by the "synaptic type" GluN1/2 NMDAR [36].…”
Section: Potentiation Of Glutamate On the Cytotoxicity Of Homocysteinementioning
confidence: 99%
See 3 more Smart Citations
“…Previously, Lecleric et al evidenced the occurrence of NMDA receptor in PC12 cells and concluded that PC12 cells express predominantly the splice variant NMDAR1-4a and smaller amounts of NMDAR1-1a, NMDAR1-2a, and NMDAR1-3a [35]. More recently, Sibarov et al implicated that GluN2A subunit-containing NMDA receptors as the preferential neural targets of Hcy [36]. Moreover, Hcy has been confirmed not only to be Ca 2+ -and NMDA receptor-dependent, but also Ca 2+ -independent, mainly mediated by the "synaptic type" GluN1/2 NMDAR [36].…”
Section: Potentiation Of Glutamate On the Cytotoxicity Of Homocysteinementioning
confidence: 99%
“…More recently, Sibarov et al implicated that GluN2A subunit-containing NMDA receptors as the preferential neural targets of Hcy [36]. Moreover, Hcy has been confirmed not only to be Ca 2+ -and NMDA receptor-dependent, but also Ca 2+ -independent, mainly mediated by the "synaptic type" GluN1/2 NMDAR [36]. Suggestively, the degree of binding by different ligands like Glu and Hcy for these receptor subunits and the outcome responses may be synergistically additive on one hand, but competitively expelling on the other hand.…”
Section: Potentiation Of Glutamate On the Cytotoxicity Of Homocysteinementioning
confidence: 99%
See 2 more Smart Citations
“…Evidence is increasing that disturbed biosynthesis or breakdown of amino acid neurotransmitters and hence pre-and/or postsynaptic dysfunction play an important role in many other inherited metabolic diseases. For instance, significant dysfunction of glutamatergic and/or GABAergic metabolism and signaling is known or thought to be involved in urea cycle disorders (Braissant 2010), isolated sulfite oxidase and molybdenum cofactor deficiency (Kumar et al 2017), homocystinurias (Poddar et al 2017;Sibarov et al 2016), branched-chain 2-ketoacid dehydrogenase kinase (Novarino et al 2012), maple syrup urine disease (Zinnanti et al 2009), GABA transaminase deficiency (Koenig et al 2017), glutamine synthetase deficiency (Häberle et al 2005), pyridoxine-dependent epilepsy (Mills et al 2006), guanidinoacetate methyltransferase deficiency (Schulze et al 2016), mucopolysaccharidosis IIIA (Dwyer et al 2017), and disorders of energy metabolism such as pyruvate carboxylase deficiency (Ortez et al 2013). Although amino acid disorders are among the earliest identified inherited metabolic diseases, the delineation of the synaptic disorder underlying the metabolic diseases has long been neglected and remains more fully examined.…”
Section: Discussionmentioning
confidence: 99%